Measuring near stereopsis - Vancleef, K; Read, J (MA Healthcare, 2017)
Stereo vision or stereopsis is the ability to perceive the relative depth of objects based on binocular disparity. Binocular disparity is the small difference in angles between images of objects in left and right eyes. Several conditions need to be met for the brain to achieve stereopsis. First, alignment of the eyes is necessary. Second, good visual acuity in each eye is essential. Third, stereoscopic vision can only be achieved by simultaneous perception and superimposition of both images on each retina and fusion of both images into one. Because stereo vision depends upon good vision in both eyes, excellent oculomotor control and the development of binocular brain mechanisms, it is often regarded as the gold standard for binocular visual function. Stereopsis is not present at birth but develops in the first months of life. That full-term and pre-term children develop stereopsis at the same age post-birth shows that the development depends on visual experience rather than biological maturation of the system. In the early months of life, we develop coarse stereopsis, which operates on high contrast lines and edges and enables us to align our eyes. Alignment then permits the development of fusion and fine stereopsis. Fine stereopsis works over a much shorter range of disparities but enables us to make very fine depth judgments even in densely textured surfaces, such as grass or tree bark, where there are few or no depth cues monocularly.